Monte Cassino the story of the most controversial battle of World War II - Hapgood, David; Richardson, David 1935- (Da Capo Press, 2002)
In trade paperback for the first time, the gripping story of one of the greatest Allied blunders--the bombing and destruction of an ancient Italian abbey
Originally published: Congdon & Weed, 1984. Reprinted with a new afterword by the authors
Keywords: Montecassino (Monastery) / Siege, 1944; Cassino, Battle of, Cassino, Italy, 1944; Montecassino (Monastery); Cassino, Battle of (Italy : 1944); Siege of Montecassino Monastery (1944); Italy / Cassino; 1944